Intraoperative laser angiography in bladder exstrophy closure: A simple technique to monitor penile perfusion. Issue 6 (December 2022) - Kaefer, Martin; Saad, Kahlil; Gargollo, Patricio; Whittam, Benjamin; Rink, Richard; Fuchs, Molly; Bowen, Diana; Reddy, Pramod; Cheng, Earl; Jayanthi, Rama; ,
Summary: Background: The successful repair of Bladder Exstrophy remains one of the biggest challenges in Pediatric Urology. The primary focus has long been on the achievement of urinary continence. Historically there has been less focus on early penile outcomes. To this end we have incorporated penile perfusion testing using intraoperative laser angiography in to our operative approach. Objective: We hypothesize that assessment of penile perfusion at various points in the procedure is a feasible technique that may assist in decision making during the repair of this complex condition. This will reduce the risk of tissue compression and potential loss of penile tissue that has been reported to occur as a complication of the procedure. Study design: Consecutive patients presenting with bladder exstrophy were evaluated at four stages of their operation (i.e. following induction of anesthesia, after bladder mobilization, following internal rotation of the pubis and at the end of the procedure) by infusing indocyanine green (ICG) at a dose of 1 mg per 10 kg body weight. Measurements were taken at 80 s post infusion and the medial thigh served as the reference control. Postoperative penile viability was evaluated by visual inspection and palpation three months following the procedure. Results: Eight consecutive patients were included in this study. Perfusion was easy to measure and posed no significant technical difficulties. Penile perfusion increased slightly following bladder dissection. Internal rotation of the hips with apposition of the symphysis pubis resulted in an average 50% reduction in penile blood flow. Patients undergoing CPRE experienced an additional mean 33% drop in blood flow. In all eight cases the penis was symmetric and healthy with no sign of tissue loss at three months follow up. Conclusions: This pilot study demonstrates that the measurement of penile perfusion utilizing intraoperative laser angiography is easy to employ and should be considered a reasonable adjunct to tissue assessment in this complex condition. Marked reduction in penile blood flow may occur without any outward clinical signs. Penile perfusion is markedly reduced by apposition of the symphysis pubis and, in the immediate postoperative period, there may be further reduction in penile blood flow with CPRE as opposed to a staged repair. Future correlation with measures of penile viability and function are needed to define the clinical utility of this modality. Summary table. Image 1